2020
DOI: 10.3390/mi11050488
|View full text |Cite
|
Sign up to set email alerts
|

Large-Field-of-View Visualization with Small Blind Spots Utilizing Tilted Micro-Camera Array for Laparoscopic Surgery

Abstract: Existing laparoscopic surgery systems use a single laparoscope to visualize the surgical area with a limited field of view (FoV), necessitating maneuvering the laparoscope to search a target region. In some cases, the laparoscope needs to be moved from one surgical port to another one to detect target organs. These maneuvers would cause longer surgical time and degrade the efficiency of operation. We hypothesize that if an array of cameras can be deployed to provide a stitched video with an expanded FoV and sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Kim et al [ 25 ] reported that RPLS for gastric cancer is not only safe and feasible but also has a shorter learning curve, similar to our findings. This is partly because RPLS has no effect on the surgical field, surgical area judgment, and tumor resection, thereby confirming the safety and clinical efficacy of the procedure[ 26 ].…”
Section: Discussionmentioning
confidence: 98%
“…Kim et al [ 25 ] reported that RPLS for gastric cancer is not only safe and feasible but also has a shorter learning curve, similar to our findings. This is partly because RPLS has no effect on the surgical field, surgical area judgment, and tumor resection, thereby confirming the safety and clinical efficacy of the procedure[ 26 ].…”
Section: Discussionmentioning
confidence: 98%
“…To calculate the field of view value, we use the trigonometry Equation (1), and all we need to do is apply the procedure shown in Figure 5. It is essential to understand that FOV follows the focal length of the lens (FL) and depends on the spatial range of the video camera sensor [34][35][36]. In Figure 6, the FOV is angle Q in the right triangle PQR.…”
Section: V2 Camera Field Of Viewmentioning
confidence: 99%